Correction: Tyson, G.; Wild, J. Post-Traumatic Stress Disorder Symptoms among Journalists Repeatedly Covering COVID-19 News. Int. J. Environ. Res. Public Health 2021, 18, 8536 - Gabriella Tyson (MDPI AG, 2021)
In the original article [...]